The Trypanosoma cruzi pleiotropic protein P21 orchestrates the intracellular retention and in-vivo parasitism control of virulent Y strain parasites - Silveira, Anna Clara Azevedo; Uombe, Nelsa Paula Inácio; Velikkakam, Teresiama; Borges, Bruna Cristina; Teixeira, Thaise Lara; de Almeida, Vitelhe Ferreira; Torres, Jhoan David Aguillon; Pereira, Cecília Luiza; de Souza, Guilherme; Teixeira, Samuel Cota; Servato, João Paulo Silva; Silva, Marcelo José Barbosa; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
P21 is a protein secreted by all forms of Trypanosoma cruzi (T. cruzi) with recognized biological activities determined in studies using the recombinant form of the protein. In our recent study we found that the ablation of P21 gene decreased Y strain axenic epimastigotes multiplication and increased intracellular replication of amastigotes in HeLa cells infected with metacyclic trypomastigotes. In the present study, we investigated the effect of P21 in vitro using C2C12 cell lines infected with tissue culture-derived trypomastigotes (TCT) of WT and P21 knockout (TcP21 -/-) Y strain, and in vivo using an experimental model of T. cruzi infection in BALB/c mice. Our in vitro results showed a significant decrease in the host cell invasion rate by TcP21 -/-parasites as measured by Giemsa staining and cell count in bright light microscope. qPCR analysis showed that TcP21 -/-parasites multiplied intracellularly to a higher extent than the scrambled parasites at 72 hours post-infection. In addition, we observed a higher egress of TcP21 -/-trypomastigotes from C2C12 cells at 144 and 168 hours post-infection. Mice infected with Y strain TcP21 -/-trypomastigotes displayed higher systemic parasitemia, heart tissue parasite burden and several histopathological alterations in heart tissues compared to control animals infected with scrambled parasites. Therewith, we propose that P21 is important in the host-pathogen interaction during invasion, cell multiplication and egress, and may be part of the mechanism that controls parasitism and promotes chronic infection without patent systemic parasitemia.